Screw dislocations around voids of any shape: A generalized numerical approach - Abu Bakar Siddique; Tariq A. Khraishi (Forces in Mechanics, 2021)
Analytical solutions for dislocations around multiple interacting free surfaces are strictly case-specific (they depend on the exact dislocation location and number and geometry of voids/free surface). This is because they rely on the precise placement of image (fictitious) dislocations, and thus can end up being very complicated in their formulation. The current article presents a general numerical scheme based on the collocation point method. The proposed method is capable of generating solutions for dislocations around multiple interacting free surfaces of any shapes or geometries. The paper also furnishes verification of the developed methodology and new results.